Improving knowledge and decreasing depressive symptoms in caregivers of children with asthma through the asthma academy: A randomized controlled trial. (November 2021) - Foronda, Cynthia; Gonzalez, Juan M.; Snowden, Kenya; Prather, Susan; Majilton, Catalina; Weisman, Alejandra; Parmeter, Sandra; Herrera, Angela; Gattamorta, Karina A.; Gonzalez, Juan E.; Downs, Charles; Hooshmand, Mary; et al.
Highlights: Caregiver mental health correlates directly with child outcomes. Remotely conducted education and telehealth was feasible and acceptable to low-income caregivers. Virtual education increased caregiver asthma knowledge and decreased depresive symptoms. More caregiver education is needed in the area of medication administration. Abstract: Background: Caregivers of children with asthma demonstrate higher levels of anxious and depressive symptoms when compared to caregivers of healthy children. Objectives: The objectives of this study were to: 1) Evaluate feasibility and acceptability of two nurse-led, remotely offered interventions for caregivers of children with asthma; 2) Compare effectiveness of two interventions (a virtual education session and a virtual education session supplemented with a telehealth visit) in relation to caregiver outcomes, and 3) Assess the preliminary effect of the interventions on caregivers' knowledge of asthma, sleep, anxiety and depressive symptoms. Methods: A mixed methods approach was used inclusive of a qualitative, descriptive design and randomized controlled trial design. Caregivers were provided virtual education and telehealth visits and evaluated from pre-posttest. Results: The intervention was found to be feasible and acceptable. Both the virtual education session and telehealth visit were effective. The intervention had a significant effect on caregiver's asthma knowledge and depressive symptoms ( p <.05), but did not affect caregiver's sleep or anxiety. Qualitative analysis of the virtual educational session revealed themes of 1) valuable learning experience, 2) more medication education needed, and 3) appreciated remote format. Qualitative analysis of the telehealth visits revealed themes of 1) educational, helpful, and worthwhile and 2) virtual offering was easy and convenient. Conclusions: Remotely conducted, nurse-led interventions such as virtual education sessions and telehealth visits are a feasible, acceptable, and effective way to improve caregiver outcomes.